Perceived Containment as a Mediator in the Association between Callous-unemotional Traits and Behavioral Problems in Detained Youth. Issue 4 (2nd October 2021) - Nowalis, Sarah; Pederson, Casey A.; Fite, Paula J.; Tampke, Elizabeth C.; Griffith, Rebecca L.
ABSTRACT: Perceived containment, the belief that authorities can effectively set limits on behavior, may explain why behavioral interventions produce moderate effects in youth exhibiting callous-unemotional traits. Examining whether callous-unemotional traits and perceived containment work together to confer risk for antisocial behaviors has implications for both screening and intervention in detained populations. In a sample of detained youth ( Mage = 15.94; 70.4% Male), path analyses indicated that perceived containment mediated the association between callous-unemotional traits and behavioral problems characterized by challenging the authority of facility staff. Implications for screening and identification of individuals in need of additional support as well as a potential cognitive target for intervention are discussed.